How to score sedation and adjust the administration rate of sedatives in horses: a literature review and introduction of the Ghent Sedation Algorithm - Schauvliege, Stijn; Cuypers, Charlotte; Michielsen, Anneleen; Gasthuys, Frank; Gozalo-Marcilla, Miguel [UNESP] (Elsevier, 2019)
Objective: To summarize the different methods used to assess sedation and/or adjust the dose or administration rate of alpha-2 agonists in horses and to propose an algorithm to adjust the administration rate of a constant rate infusion of an alpha-2 agonist in horses. Databases used: PubMed and Web of Science; search terms: horse, sedation and score. Conclusions: Most authors distinguish between sedation depth, sedation quality and degree of ataxia. These three features are evaluated using scoring systems similar to those classically used to assess pain, i.e. simple descriptive scales, numerical rating scales (NRS), visual analogue scales and/or multifactorial sedation scales. In addition, head height above the ground is often used as a measure of the depth of sedation. Very few authors have described how to adjust the administration rate or dose of alpha-2 agonists. Based on the available literature, the Ghent Sedation Algorithm was developed, which assigns scores (NRS) for degree of ataxia, sedation depth and surgical conditions, and uses these to prescribe changes in the administration rate of constant rate infusions of alpha-2 agonists. Studies are needed to validate this algorithm.
Keywords: Ghent Sedation Algorithm; horse; score; sedation